THE BIOCHEMICAL PHENOTYPE OF THE ASPIRIN TRIAD - Ерстенюк, Г. М.; Попович, В. І.; Кошель, І. В.; Фіщук, Р. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the article the modern conceptual opinion upon etiopathoqenesis of the aspirin triad as the metabolic disease with the changes of etiopathogenesis is expressed. The hypersensitivity end intolerance of acetylsalicylic acid up to the present are explained by the nonimmune mechanism. Thus, the sensitivity to the qiven preparathion neither in bronchial asthma nor in nasal poliposis was not defined. The etiopathoqentsis was connected with the disorders in the metabolism of the arachidonic acid and the cause of such disorders was believed to be connected with the aspirin use or the use of the other nonsteroidal anti-inflammatory preparations. As the result of investiqations , the biochemical phenotype of the diseases was established. Primary qenetically determined and nonstimulated by the aspirin use the reduction of the activity of cyclooxygenase enzyme activates the “go round ways” of the arachidonic acid’s metabolism and the accumulated active metabolities. Jheir bioloqical effects are the main etiopathogenetic links of chronic eosinophile inflammation in the mucosa of the respiratory tract and the formation of chronic poliposis of rhinosinusitis and the bronchial asthma.